MECHANISM OF BORAX CRYSTALLIZATION USING CONDUCTIVITY METHOD - Suharso Suharso (Universitas Gadjah Mada, 2008)
The kinetics of crystal growth of borax has been studied by using conductivity method at temperature of 25 °C and at various relative supersaturations. It was found that the growth rate increases with increasing supersaturation. At low concentration, growth occurs via a spiral growth mechanism and at high concentration birth and spread is the principal mechanism operating.